Lead independent directors and investment efficiency - Rajkovic, Tijana (Journal of Corporate Finance, 2020)
I show that the presence of a lead independent director on the corporate board is positively associated with investment efficiency. The result is more pronounced for firms with weaker corporate governance standards, less transparent financial disclosure, and greater financial constraints. The lead director presence is negatively associated with overinvestment (underinvestment) for firms with large cash balances and low leverage (high cash flow volatility). Moreover, the lead director investment-related committee membership as well as CEO power matter in this setting. The lead director board role is also positively associated with future firm performance.